Do Entrepreneurship Education and Use of Social Media among Students Affect Entrepreneurial Interest through Entrepreneurial Motivation? - Andi Mulyadi Radjab; Muh. Yahya; Andika Isma; Salim Diarra; Soussou Raharimalala (EduLine: Journal of Education and Learning Innovation, 2023)
This study aims to determine whether the influence of entrepreneurship education and the use of social media among students affects entrepreneurial interest through entrepreneurial motivation. This type of research is quantitative research. The research design uses a survey method with a questionnaire as a data collection instrument. The study population was all Entrepreneurship Students of Universitas Negeri Makassar which amounted to 427 students. While the sampling technique uses Proportional Random Sampling technique, which is calculated using the Slovin formula with a sample size of 84 respondents or 22% of the total population. The research method used in this research is quantitative. The results showed that indirectly entrepreneurship education and the use of social media affect the interest in entrepreneurship with entrepreneurial motivation as an intervening variable. However, for the direct effect of only entrepreneurship education and the use of social media on entrepreneurial interest that has no effect, while for the effect on entrepreneurial motivation there is a significant effect. This research can be a source of information or reference for teaching staff or lecturers so that they can direct and guide students regarding the development of entrepreneurial interests, students are also expected to deepen their interest in business management so that they are not only focused on the knowledge produced, but also able to do business and develop it.